Entrepreneurial intention of UiTM students and the mediating role of entrepreneurship education / Saw Imm Song, Santhanamery Thominathan and Nor Aminin Khalid - Song, Saw Imm; Thominathan, Santhanamery; Khalid, Nor Aminin (2021)
The emphasis on entrepreneurship by the Malaysian government clearly displays their effort in strengthening the entrepreneurial development in the country, which is expected to boost the economy by creating more jobs and generating new incomes. The idea is extended to local higher education institutions so as to nurture and to sustain entrepreneurial engagement among the students through formal entrepreneurial programs. The initiatives are expected to help in reducing graduate unemployment level in the country. Despite all the effort taken by the government, the uptake of entrepreneurship among young minds is still low, and there is growing unemployment in the country. Thus, this study aims to determine the factors that affect entrepreneurial intentions among UiTM graduating students and the mediating effect of entrepreneurship education towards entrepreneurial intention through attitude, perceived behaviour control and self-efficacy. The sample consists of 429 UiTM students who have taken the entrepreneurship course. Factor analysis and Partial Least Squares methods were used to analyse the data. The findings reveal a significant relationship of attitude, perceived behaviour control and entrepreneurship education towards entrepreneurial intention, while self-efficacy was insignificantly related. However, the study found that entrepreneurship education partially mediates the relationship between attitude and perceived behaviour control towards entrepreneurship intention and a full mediation on self-efficacy. The findings will help the policymakers or the higher education institutes in developing a suitable policy and program in promoting entrepreneurship to the university graduates at the national level.